Use of negative pressure wound therapy as an adjunct to the treatment of extremity soft-tissue sarcoma with ulceration or impending ulceration - CHEN, YU (Oncol Lett, 2016)
Major wound complications of the extremities, following wide tumor resection and reconstruction for soft-tissue sarcomas (STSs), remain a challenge for limb-sparing surgery. Furthermore, STSs with ulceration or impending ulceration predispose patients to an increased risk of post-operative infection. The present study was conducted to assess the efficacy of negative pressure wound therapy (NPWT) in preventing wound complications associated with surgical treatment of STSs with ulceration or impending ulceration, in patients treated between February 2012 and January 2013. A total of 5 patients, with a mean age of 48 years (range, 24–68 years), were enrolled in the present study. The diagnoses consisted of undifferentiated pleomorphic sarcoma (n=2), leiomyosarcoma (n=1), synovial sarcoma (n=1) and epithelioid sarcoma (n=1). According to American Joint Committee on Cancer criteria, 3 cases were stage III tumors, and the remaining 2 cases were of stages IIA and IIB, respectively. A total of 3 patients exhibited ulceration at diagnosis, and the remaining patients demonstrated impending ulceration. The mean wound area following wide resection of the tumor was 73 cm(2) (range, 45–110 cm(2)). A continuous suction mode, with pressures measuring −200 to −300 mmHg, was used for 7–10 days on the soft-tissue defects as preparation for wound closure. Soft-tissue reconstruction included muscle flaps (n=2) and skin grafts (n=5). No major wound complications occurred. Post-operative functional and cosmetic outcomes were acceptable. A single patient demonstrated local recurrence 12 months after surgery and re-excision of the tumor was performed. All patients remained alive at the conclusion of follow-up, with a mean follow-up time of 26 months (range, 12–36 months). The present study demonstrated that NPWT is effective and safe when used as an adjunct to wound closure following resection of extremity STS with ulceration/impending ulceration.